R&D trends on direct formic acid fuel cells - Kwon, Y.; Han, J.; Kim, J. (2008)
Recently, as a demand for the portable device is surged, there are needs to develop a new fuel cell system for replacing the conventionally used secondary battery. For this purpose, it becomes important to develop direct formic acid fuel cell (DFAFC) that uses formic acid as a fuel. The formic acid can offer typical advantages such as excellent non-toxicity of the level to be used as food additive, smaller crossover flux through electrolyte, and high reaction capability caused by high theoretical electromotive force (EMF). With the typical merits of formic acid, the efforts for optimizing reaction catalyst and cell design are being made to enhance performance and long term stability of DFAFC. As a result, to date, the DFAFC having the power density of more than 300 mW/cm2 was developed. In this paper, basic performing theory and configuration of DFAFC are initially introduced and future opportunities of DFAFC including the development of catalyst for the anode electrode and electrolyte, and design for the optimization of cell structure are discussed.